2019
DOI: 10.1111/jen.12632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host use adaptation on the dispersal propensity of Callosobruchus maculatus

Abstract: Local adaptation can lead to significant differences in host use that may influence population growth and spread. Here, we test the potential for adaptation of one behavioural component (host acceptance) to lead to cross‐adaptation for a separate behavioural component (dispersal propensity) using the cowpea seed beetle, Callosobruchus maculatus. C. maculatus originating from the same source population were subjected to selection for host use by rearing them for over 40 generations on either the preferred host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Bean beetles are responsive to these cues, affecting host preference (Messina, 2004;Messina et al, 2018). Most studies show that females preferred their natal host when given a choice (Messina and Slade, 1997;Boeke et al, 2004;Paukku and Kotiaho, 2008;Rova and Björklund, 2011;Bergeron et al, 2019), suggesting a learned response, but some studies did not find a preference (Mainali et al, 2015;Bergeron et al, 2019). Therefore while many studies have demonstrated the capability of herbivorous insects to learn during oviposition (Jones and Agrawal, 2017), the existence of such a learned response in Callosobruchus is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Bean beetles are responsive to these cues, affecting host preference (Messina, 2004;Messina et al, 2018). Most studies show that females preferred their natal host when given a choice (Messina and Slade, 1997;Boeke et al, 2004;Paukku and Kotiaho, 2008;Rova and Björklund, 2011;Bergeron et al, 2019), suggesting a learned response, but some studies did not find a preference (Mainali et al, 2015;Bergeron et al, 2019). Therefore while many studies have demonstrated the capability of herbivorous insects to learn during oviposition (Jones and Agrawal, 2017), the existence of such a learned response in Callosobruchus is uncertain.…”
Section: Introductionmentioning
confidence: 99%